1969
DOI: 10.1128/aem.18.5.906-910.1969
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Coagulase Clotting by Trypsin Inhibitor

Abstract: Egg white trypsin inhibitor activated coagulase clotting when added to a final concentration between 2 and 60 mg/ml. The greatest increase in clotting rate was observed in reaction mixtures containing the lowest concentrations of serum and plasma. Maximal activation was reached with 40 mg of trypsin inhibitor per ml when either serum or plasma was used as the source of coagulase-reacting factor (CRF). The increased rate of clotting is partly due to inhibition of plasmin. Freezing and thawing reduced plasma clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…They found the reaction time decreases with increases in plasma concentration until a concentration of about 4 0 %~ Stutzenberger et al (1966) concluded t h a t the relative activity of the coagulase increases with the plasma concentration up to a concentration of 2?6 as determined nephelometrically. This result differed sharply from those of Orth et al (1969), but it must be clarified that the source of plasma as well as the assay procedure were completely different. The activity of the reaction also increased with the fibrinogen concentration up to about 2.5 mg/ml.…”
Section: Factors Influencing Staphylocoagulase Detectioncontrasting
confidence: 62%
See 2 more Smart Citations
“…They found the reaction time decreases with increases in plasma concentration until a concentration of about 4 0 %~ Stutzenberger et al (1966) concluded t h a t the relative activity of the coagulase increases with the plasma concentration up to a concentration of 2?6 as determined nephelometrically. This result differed sharply from those of Orth et al (1969), but it must be clarified that the source of plasma as well as the assay procedure were completely different. The activity of the reaction also increased with the fibrinogen concentration up to about 2.5 mg/ml.…”
Section: Factors Influencing Staphylocoagulase Detectioncontrasting
confidence: 62%
“…The plasmin thus formed causes fibrinolysis (proteolytic degradation of the fibrinogen clot) which results in the disappearance of the clot observable during coagulase test a n d therefore can lead to false negative reactions (Orth et al 1971). This activity can be prevented by adding soybean trypsin inhibitor into the assay system (Hutchinson 1962;Orth et al 1969).…”
Section: Factors Influencing Staphylocoagulase Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A partially purified protein preparation from S. aureus 265-1 was used as the source of SK and MF. This material possessed coagulas activity; its preparation was described elsewhere (14). Serum and plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, 0.35-ml eluant fractions were collected, egg white trypsin inhibitor (EWTI, Calbiochem trypsin inhibitor; egg white, B grade, each milligram inhibits approximately 0.7 mg of trypsin) was added to give a final concentration of 40 mg/ml, and the fractions were assayed for CRF by determining coagulase activity at 15-min intervals by the method of Orth et al (9). Fibrinolysis was determined by making periodic readings for as long as 24 hr and recording the degree of fibrin gel formation by using the method of Turner and Schwartz (13).…”
mentioning
confidence: 99%